What's in the Chinese Babyface? Cultural Differences in Understanding the Babyface - Zheng, Wenwen; Yang, Qian; Peng, Kaiping; Yu, Feng (Frontiers in Psychology, 2016)
We investigated the cultural differences in understanding and reacting to the babyface in an effort to identify both cultural and gender biases in the universal hypothesis that the babyfaced individuals are perceived as naïve, cute, innocent and more trustworthy. Sixty-six Chinese and sixty-six American participants were required to evaluate Chinese faces selected from the Chinese Academy of Sciences (CAS) - Pose, Expression, Accessories, and Lighting (PEAL) Large-Scale Chinese Face Database. In our study, we applied Active Shape Models, a modern technique of machine learning to measure facial features. We found some cultural similarities and also found that a Chinese babyface has bigger eyes, higher eyebrows, a smaller chin and greater WHR (Facial width-to-height ratio), and looks more attractive and warmer. New findings demonstrate that Chinese babyfaces have a lower forehead and closer pupil distance. We found that when evaluating the babyfacedness of a face, Chinese are more concerned with the combination of all facial features and American are more sensitive to specific highlighted babyfaced features. The Chinese babyface tended to be perceived as more babyfaced for American participants, but not less competent for Chinese participants.